Lesotho--development in a challenging environment : a joint World Bank-African Development Bank evaluation - Hassan, Fareed M. A.; World Bank.; African Development Bank. (Abidjan [Côte d'Ivoire] : African Development Bank ; Washington, DC : World Bank, 2002)
This country assistance evaluation was prepared in collaboration with the African Development Bank Group
At head of title: World Bank Operations Evaluation Department, African Development Bank Operations Evaluation Department.
Includes bibliographical references (p. 111-112).
osc 2/09/2021
Loans
Keywords: Economic assistance; Lesotho; Lesotho